Large-Scale Generation of Human Allospecific Induced Tregs With Functional Stability for Use in Immunotherapy in Transplantation - Alvarez-Salazar, Evelyn Katy; Cortés-Hernández, Arimelek; Arteaga-Cruz, Saúl; Alberú-Gómez, Josefina; Soldevila, Gloria (Frontiers in Immunology, 2020)
Regulatory T cells play an important role in the control of autoimmune diseases and maintenance of tolerance. In the context of transplantation, Tregs have been proposed as new therapeutic tools that may induce allospecific tolerance towards the graft, avoiding the side effects induced by generalized immunosuppressors. Although most clinical trials are based on the use of thymic Tregs cells in adoptive therapy, some reports suggest the potential use of in vitro induced-Tregs, based on their functional stability under inflammatory conditions, indicating an advantage in a setting of allograft rejection. The aim of this work was to generate and expand large numbers of allospecific Tregs which maintain stable suppressive function in the presence of pro-inflammatory cytokines. Dendritic cells were derived from monocytes isolated from healthy donors and were co-cultured with CTV-labeled naïve T cells from unrelated individuals, in the presence of TGF-β1, IL-2 and Retinoic Acid. After 7 days of co-culture, proliferating CD4+CD25hiCTV- cells (allospecific induced-Tregs) were sorted and polyclonally-expanded for 6 weeks in the presence of TGF-β1, IL-2 and Rapamycin. After 6 weeks of polyclonal activation, iTreg cells were expanded 230,000 times, giving rise to 4,600 millions of allospecific induced Tregs. Allospecific iTregs were able to specifically suppress the proliferation of autologous CD4+ and CD8+ T cells in response to the allo-MoDCs used for iTreg generation, but not to third party allo-MoDCs. Importantly, 88.5% of the expanded cells were CD4+CD25+FOXP3+, expressed high levels of CCR4 and CXCR3 and maintained their phenotype and suppressive function in the presence of TNF-α and IL-6. Finally, analysis of the methylation status of the FOXP3 TSDR locus demonstrated a 40% demethylation in the purified allospecific iTreg, previous to the polyclonal expansion. Interestingly, the phenotype and suppressive activity of expanded allospecific iTregs were maintained after 6 weeks of expansion, despite an increase in the methylation status of the FOXP3 TSDR. In conclusion, this is the first report that demonstrates a large-scale generation of allospecific iTregs which preserve a stable phenotype and suppressor function in presence of pro-inflammatory cytokines and pave the way for adoptive cell therapy with iTregs in transplanted patients.